2010
DOI: 10.1016/j.otsr.2010.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Distal femoral varus osteotomy outcome: Is associated femoropatellar osteoarthritis consequential?

Abstract: Level IV. Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 17 publications
0
53
0
9
Order By: Relevance
“…The Kellgren-Lawrence (K-L) classification was utilized to stratify patients in 2 studies (mean, 1.76 5 and 2.3 22 . ), and the Ahlb盲ck classification was used in 1 study (mean, 2.75 25 ) ( Table 2 ). The opening-wedge group was more heterogeneous regarding rehabilitation protocol.…”
Section: Resultsmentioning
confidence: 99%
“…The Kellgren-Lawrence (K-L) classification was utilized to stratify patients in 2 studies (mean, 1.76 5 and 2.3 22 . ), and the Ahlb盲ck classification was used in 1 study (mean, 2.75 25 ) ( Table 2 ). The opening-wedge group was more heterogeneous regarding rehabilitation protocol.…”
Section: Resultsmentioning
confidence: 99%
“…However, its indication remains controversial when associated patellofemoral osteoarthrosis is present. Zarrouk et al [153] conducted a retrospective study of 22 knees and concluded that the association of patellofemoral osteoarthritis does not affect the functional results. No studies exist examining the effect of varus and femoral derotation osteotomies on realignment and patellofemoral osteoarthrosis.…”
Section: Other Bony Proceduresmentioning
confidence: 99%
“…Good survival rate at 5-year follow-up are reported in literature also for opening-wedge DFO, ranging from 74% to 100% (11,15,22,34,44,45 All the osteotomies in the first group healed within nine months while there were four cases of non-union in the second group. They concluded that this difference was not statistically significant but seems that it could be significant if more patients were enrolled in the study (47 In patients with failed DFOs, performing a total knee arthroplasty (TKA) is an highly demanding procedure with an increased risk of poor results (7).…”
Section: Resultsmentioning
confidence: 81%
“…A varus opening wedge DFO may reduce the Q angle unloading the patellofemoral lateral compartment (3). Zarrouk et al, in their analysis of 26 DFOs, demonstrated that patients with patellofemoral osteoarthritis had comparable results to the others patients at the final follow-up (15). Although some authors consider symptomatic patellofemoral arthritis an absolute (13) or relative contraindication to DFO (12,16), considering the theoretical mechanical advantages and Zarrouk's results, moderate patellofemoral arthritis may not be considered an absolute contraindication to DFO (15,17).…”
Section: Indications and Contraindicationsmentioning
confidence: 99%